Determinants of Distribution Logistics in the Construction Industry - Bukova Bibiana; Brumercikova Eva; Kondek Pavol (Open Engineering, 2017)
Global business is currently still influenced by the economic crisis and the economic development in each country of the EU. The construction sector is among the most affected sectors of the national economies. The production of building material is a part of the construction industry. Several companies of this sector in the European Union use business logistics effectively. The overall efficiency of the company is influenced by many various external and internal determinants, especially the distribution logistics.